Legal Consequences of Notarial Negligence in the Preparation of Credit Deeds and Banking Security Deeds - Khairuddin; Bambang Fitrianto; Dahlan (CV. Era Digital Nusantara, 2026)
This study aims to examine the legal consequences of notarial negligence in the preparation of credit deeds and banking security deeds, as well as to identify the forms of inaccuracies that arise in notarial practice at the office of Notary Khairuddin Rasyid in Batam City. The research employs a normative juridical method combined with an empirical approach, involving the analysis of statutory regulations, legal doctrines, and practical implementation of deed drafting. The findings indicate that notarial negligence, both in formal and substantive aspects of deeds, may result in diminished evidentiary value, the potential nullification or voidability of deeds, and legal liability risks for notaries. This study underscores the necessity of applying the prudential principle, professionalism, and strict legal compliance to ensure legal certainty and protection for parties involved in banking transactions.